Utilização do óleo de coco babaçu na lubrificação de caixa de transmissão por engrenagens para protótipo Baja SAE - Rocha, Plinio Pereira (2022)
The use of oil as a lubricant in gearboxes serves to reduce friction and wear on tooth surfaces, in addition to protecting the mechanism from corrosion. Commercial oils are commonly of mineral or synthetic origin, which has generated great concern regarding the environmental impact and occupational health. Some studies point out possibilities of using biodegradable oils to replace the current ones, burdening such impacts. In view of this, the present work proposes to develop a vegetable based lubricating oil, from the extraction of babaçu coconut (Attalea speciosa). To validate the lubricant, comparative tribological evaluations were carried out between commercial lubricant, based on synthetic, and vegetablebased lubricant. The tests were carried out on a tribological test bench, a reciprocal linear tribometer, where the specimen was subjected to various mechanical stresses to simulate the work of the gears. Regarding wear on the specimen, the following items were evaluated: roughness, weight of the specimen, area of wear and coefficient of friction. Based on the results of the tribological tests carried out, it was noted that wear is directly linked to lubrification and that babaçu coconut oil had a higher fiction coefficient compared to commercial oil but has the potencial to be uses as a lubrificant.